Mapping distribution of Capsicum annum var. chinense in Tana Toraja and surrounding districts (Indonesia) based on fruit morphology - HAFIZHAH AL-AMANAH; RINALDI SJAHRIL; FERANITA HARING; MUHAMMAD RIADI; SITI HALIMAH LAREKENG (Society for Indonesian Biodiversity, 2022)
Abstract. Al-Amanah H, Sjahril R, Haring F, Riadi M, Larekeng SH. 2021. Mapping distribution of Capsicum annum var. chinense in Tana Toraja and surrounding districts (Indonesia) based on fruit morphology. Biodiversitas 23: 982-991. Katokkon pepper (Capsicum annum var. chinense) is one of the many Capsicum genetic resources still cultivated in small farms and home gardens in Tana Toraja, North Toraja, Enrekang and Mamasa districts of Indonesia. This study was conducted to identify genetic diversity of C. annum var. chinense pepper based on fruit characteristics as morphological markers in the endemic area. The study location was determined by purposive sampling. Morphological characterization was carried out by observing quantitative and qualitative characters. Results showed that C. annum var. chinense was widely distributed in the districts of Tana Toraja 47% (14 sub-districts, 17 villages), North Toraja 34% (11 sub-districts, 14 villages), Enrekang 12% (3 sub-districts, 5 villages), and Mamasa 7% (2 sub-districts, 6 villages). Cluster analysis based on quantitative characters of fruit morphology from 51 accessions led to 5 dendrogram clusters with 90% similarity level. Principal Component Analysis (PCA) results had a cumulative diversity value of 75.913%. The color characteristic of fruit before ripening was light green, which turned red when mature. Cross-sections of the fruits were slightly corrugated. Fruits were pendant, and shapes were blocky. Fruit shape at pedicel attachment was truncated. Fruit shapes at the blossom end were blunt. In all the areas explored, only four common genotypes, i.e. Limbong Sangpolo or Local, Leatung 1, Leatung 2, and Jumbo were found.